A Perplexing Process: Understanding How Agricultural Producers Process Best Management Practice Information - Audrey E. H. King; Lauri M Baker (Journal of Applied Communications, 2018)
Best management practices (BMPs) are suggested practices that help agricultural producers optimize production while reducing pollution, soil erosion, and other environmental impacts. Many audiences, including scientists and policy makers, have expressed disappointment at the current level of BMP use. Elaboration likelihood model (ELM) is used to understand how people process messages. ELM states that people can process messages either centrally or peripherally. This study sought to understand how producers processed information related to BMP adoption in grazing systems. Researchers conducted qualitative, in-depth interviews with 42 beef-cattle producers in Kansas and Oklahoma. It was found producers process information both centrally and peripherally, more specifically through past experiences and visual observations. This study suggests that when promoting BMPs, communicators should use visual cues to help producers process information. More importantly communicators should utilize strategies that encourage producers to reflect on past experiences to promote central processing.
Keywords: elaboration likelihood model; best management practices; grazing